1D hydrogen engine modeling to investigate air-fuel ratio, spark timing, and water injection effects on performance and emissions - Omar Mohamed Saied; Mohamed Abdelwahab (Scientific Reports)
Abstract This study presents a comprehensive 1D modeling and simulation of a hydrogen-fueled internal combustion engine, focusing on the impacts of air-fuel ratio, spark timing, and water injection on performance and emissions. Using a single-cylinder BMW F650 GS engine as a baseline, simulations were conducted in Ricardo WAVE to evaluate engine behavior under varying conditions. Results demonstrate that hydrogen fueling reduces CO emissions to negligible levels but increases NOx emissions under specific conditions due to elevated combustion temperatures. Water injection effectively mitigates NOx formation and enhances volumetric efficiency while slightly compromising power output at high hydrogen-to-water ratios. The findings highlight hydrogen’s potential as a sustainable fuel for internal combustion engines and underline the importance of optimizing operating parameters to balance performance, efficiency, and emissions. This research contributes valuable insights into the development of cleaner, hydrogen-powered transportation solutions.